2005
DOI: 10.1097/01.ju.0000176478.17749.07
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Reactions of 5 Sling Materials and Tissue Material Detachment Strength of 4 Synthetic Mesh Materials in a Rabbit Model

Abstract: All 5 synthetic sling materials produce similar tissue reactions beginning soon after implantation. Cadaveric fascia lata persisted in tissue with remarkable perifascial fibrosis at day 30. When comparing the 4 polypropylene mesh materials; the attachment capacity of TVT was superior and that of IVS was the least of the 4. TVT was statistically better than IVS at all data points. SPARC and hernia mesh provided results similar to those of TVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 11 publications
3
22
0
6
Order By: Relevance
“…Yildirim et al . also observed marked inflammation on the early days after implantation and predominant fibrotic reaction on days 15 and 3023. Similarly, another study reported an early increase in IL-1 with peak during first week and reduced after 15 days with a sharp increase in MMP-2 around day 7 and declines thereafter24.…”
Section: Discussionmentioning
confidence: 62%
“…Yildirim et al . also observed marked inflammation on the early days after implantation and predominant fibrotic reaction on days 15 and 3023. Similarly, another study reported an early increase in IL-1 with peak during first week and reduced after 15 days with a sharp increase in MMP-2 around day 7 and declines thereafter24.…”
Section: Discussionmentioning
confidence: 62%
“…Tissue reactions to different types of synthetic materials used to repair the defects of the pelvic floor are almost established and have not been dealt with in this study (22)(23)(24)(25). It is known that, apart from the mechanical properties of the implanted material, local factors such as tissue tropism, infections and the surgical technique are directly related to the rates of extrusion (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…The recently published data indicate that the composition of the fibers, type of weave, pore size, tensile strength, flexibility of the material, and tissue response of sling materials may play a role in surgical success [23][24][25] . In an earlier animal study performed at our center, the mesh-to-tissue attachment strength of the IVS was found to be the least among different types of sling mesh materials [26] .…”
Section: Discussionmentioning
confidence: 99%